2000
DOI: 10.1054/bjoc.1999.0994
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for expert histopathological assessment of ovarian cancer and borderline tumours

Abstract: The distinction between borderline ovarian tumours (BOT) and ovarian carcinoma is made by histopathological assessment. Of 64 patients managed according to institutional BOT protocols, 27 (42%) had been referred with a diagnosis of ovarian carcinoma that was subsequently changed to BOT following histopathological review. The 70% 6-year event-free survival of the patients with a revised diagnosis was not significantly different from those who were referred with a diagnosis of BOT. This change in diagnosis is im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…9,10 Generally, in community practice pathologists favor more severe pathological diagnoses. 6,7 As a result, BOTs and BOTs associated with implants diagnosed in general practice may be associated with a better prognosis than those reported in the literature. Finally, given the relative rarity of BOTs, many reports are based on cases accumulated over long periods, which raise external validity concerns related to shifts over time in etiologic exposures, detection methods, diagnostic criteria, and treatments that could affect clinical presentations and behavior.…”
Section: Limitations Of Existing Research On Bots: External Validitymentioning
confidence: 98%
See 1 more Smart Citation
“…9,10 Generally, in community practice pathologists favor more severe pathological diagnoses. 6,7 As a result, BOTs and BOTs associated with implants diagnosed in general practice may be associated with a better prognosis than those reported in the literature. Finally, given the relative rarity of BOTs, many reports are based on cases accumulated over long periods, which raise external validity concerns related to shifts over time in etiologic exposures, detection methods, diagnostic criteria, and treatments that could affect clinical presentations and behavior.…”
Section: Limitations Of Existing Research On Bots: External Validitymentioning
confidence: 98%
“…6 Similarly, an audit of 64 cases of BOT referred to a UK institution with special expertise in gynecologic pathology between 1988 and 1997 found that 27 (42%) were misdiagnosed as ovarian carcinoma. 7 In another review of cases originally diagnosed as stage 1 or 2 ovarian carcinoma at a tertiary center , 29% of cases we reclassified as BOTs. Importantly, only 4.5% of women with tumors reclassified as BOTs died of disease as compared to 25.6% of patients with confirmed diagnoses of carcinoma.…”
Section: Limitations Of Existing Research On Bots: External Validitymentioning
confidence: 99%
“…However, LOH analysis revealed several interesting aspects of LMP as discussed above. Because histopathologic examination cannot distinguish between mucinous LMP that will not change into OC from those that are precursors of OC, 26 LOH analysis of 7q35 may be useful to discriminate between them. Conversely, we need to be vigilant in following up cases of mucinous LMP with LOH at 5q14-21 and 17q11.2 (NF1) after surgery.…”
Section: Loh Analysis In Ovarian Tissues From Different Lesionsmentioning
confidence: 99%
“…Ovarian tumors are classified as epithelial tumors, germ cell tumors, sex cord-stromal cell tumors, and metastatic tumors on the basis of tumor origin (Koonings et al, 1989).As most patients with ovarian carcinoma have distant or widespread disease at the time of diagnosis, this fact underscores the importance of early detection and improved characterization of ovarian masses and is of paramount and utmost importance in the preoperative evaluation, enabling the surgeon to anticipate carcinoma of the ovary before the operation, so that adequate procedures are planned (Hermann et al, 1987;Mugel et al, 1993;Osmers et al, 1996;Sengupta et al, 2000). Bimanual pelvic examination and serum CA-125 levels have failed to allow consistent detection of ovarian malignancy.…”
Section: Introductionmentioning
confidence: 99%